A pre-treated carbon nanotube reinforced hierarchical porous carbon microsphere composite electrode material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611061988.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]本发明的目的在于提供一种预处理碳纳米管增强分级多孔碳微球复合电极材料及其制备方法和应用,以解决现有分级多孔碳微球体系存在的电子传输路径不连续、微球之间接触电阻较大、界面结合不够稳定以及在含盐水体系中离子传输效率和循环性能受限等问题
[0023]1.本发明以分级多孔碳微球作为复合材料的主体吸附骨架,具有较高比表面积以及微孔—介孔协同分布的孔道结构。其中,微孔可提供较多离子吸附位点,增强材料的电吸附能力;介孔有利于电解液渗透和离子快速扩散,降低传质阻力。二者协同作用,有助于兼顾吸附容量与吸附速率,从而为电容去离子过程中的高效离子去除提供良好的结构基础。
Smart Images

Figure CN122907514A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of capacitive deionization electrode materials, specifically relating to a pretreated carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, its preparation method, and its application. Background Technology
[0002] Capacitive deionization technology, due to its advantages such as low energy consumption, mild operating conditions, relatively simple device structure, and regenerable electrodes, shows promising application prospects in brackish water treatment, seawater pre-desalination, industrial saline wastewater purification, and ion removal in other saline systems. This technology achieves ion removal by driving cations and anions in the solution to migrate to the corresponding electrode surface and form an electrical double layer through an applied electric field. Therefore, the specific surface area, pore structure characteristics, conductivity, and interfacial stability of the electrode material have a significant impact on its electroadsorption capacity, ion transport efficiency, and recyclability.
[0003] Existing capacitive deionization electrode materials are mostly based on carbon materials, including activated carbon, graphene, porous carbon, and carbon nanotubes. Among them, hierarchical porous carbon microspheres are considered to be electrode materials with greater application potential due to their relatively regular spherical morphology, tunable particle size distribution, and micropore-mesopore synergistic structure, which can provide favorable conditions for ion adsorption and diffusion. Hierarchical porous carbon microspheres prepared by hard template-assisted and activated pore-forming methods can usually form a multi-level pore structure that runs through the carbon framework. The micropores are beneficial for providing ion adsorption sites, while the mesopores are beneficial for promoting electrolyte penetration and ion diffusion, thereby improving the mass transfer performance of the material in the capacitive deionization process.
[0004] However, using hierarchical porous carbon microspheres alone as electrode materials still presents problems such as discontinuous electron transport paths, high contact resistance between microspheres, and unstable interfacial contacts. This is especially problematic under high salinity or long cycling conditions, which can lead to decreased adsorption rates and limited cycling performance. Carbon nanotubes, with their excellent electrical conductivity and one-dimensional network structure, are expected to form a bridging conductive network between microspheres, reducing interparticle contact resistance, shortening electron migration paths, and further improving the overall conductivity and structural stability of the composite material. Furthermore, appropriate pretreatment of carbon nanotubes can introduce oxygen-containing functional groups onto their surface, thereby improving their dispersion performance and compatibility with the carbon microsphere surface.
[0005] Therefore, it is necessary to develop a method for preparing carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode materials. While maintaining the advantages of the original pore structure of hierarchical porous carbon microspheres, the method enhances the composite interface bonding and overall conductive network construction by introducing carbon nanotubes and subsequent heat treatment. This will further improve the ion removal efficiency, mass transfer performance and cycle stability of the material in the capacitive deionization process, and expand its application in brackish water, simulated brine, industrial saline wastewater and other saline systems. Summary of the Invention
[0006] The purpose of this invention is to provide a pretreated carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, its preparation method, and its application, in order to solve the problems of discontinuous electron transport paths, large contact resistance between microspheres, unstable interfacial bonding, and limited ion transport efficiency and cycling performance in saline systems in existing hierarchical porous carbon microsphere systems.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a pretreated carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material includes the following steps:
[0009] S1. A spherical precursor was prepared by mixing a carbon source, a heteroatom source and a nano-silica template in a dispersion medium and using a hydrothermal reaction method.
[0010] S2. The spherical precursor obtained in step S1 is subjected to high-temperature carbonization, acid washing to remove the template, and activation to create pores, thereby producing fractional porous carbon microspheres; wherein, the high-temperature carbonization is the first stage of heat treatment.
[0011] S3. Carbon nanotubes are pretreated by oxidation and then dispersed in a dispersion medium. They are then mixed and composited with the hierarchical porous carbon microspheres obtained in step S2 to obtain a composite precursor.
[0012] S4. After drying the composite precursor obtained in step S3, perform a second heat treatment under an inert atmosphere to obtain a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material.
[0013] Further, in step S1, the carbon source is one or more of sugars, cellulose, furfural, phenolic compounds, and water-soluble polymeric carbon sources; the heteroatom source is one or more of boron-containing compounds and nitrogen-containing compounds; and the dispersion medium is one or more of deionized water, ethanol, and isopropanol.
[0014] Further, in step S1, the mass ratio of the carbon source, heteroatom source and nano-silica template is (20-50):(10-50):(0.5-3), the mass ratio of the carbon source and the dispersion medium is (5-15):(50-100), the hydrothermal reaction temperature is 160-200℃, and the time is 6-12h.
[0015] Further, in step S2, the spherical precursor is carbonized at high temperature in an inert atmosphere at a temperature of 900-1100℃ for 1-3 hours; the template removal is achieved by etching with acid to remove the silica template; the activation and pore formation are carried out in a N2 / CO2 mixed atmosphere at a temperature of 700-900℃ for 0.5-2 hours to obtain a hierarchical porous carbon microsphere structure with a synergistic distribution of micropores and mesopores; wherein CO2 accounts for 5%-60% of the total volume of the N2 / CO2 mixed gas, and the mixed gas flow rate is 50-500 mL / min.
[0016] Further, in step S3, the carbon nanotube oxidation pretreatment is carried out by one or more of the following methods: nitric acid treatment, sulfuric acid / nitric acid mixed acid treatment, and hydrogen peroxide treatment. The treatment temperature is 40-80℃ and the treatment time is 1-6h. The dispersion medium is one or more of the following: deionized water, ethanol, and isopropanol.
[0017] Further, in step S3, the mass ratio of the hierarchical porous carbon microspheres to the carbon nanotubes after oxidation pretreatment is 100:1-2:1; the mixing and composite conditions are: stirring at room temperature to 60°C for 1-12 hours, supplemented by ultrasonic treatment for 5-60 minutes.
[0018] Furthermore, in step S4, the second heat treatment is carried out under a nitrogen or argon atmosphere, the heat treatment temperature is 700-900℃, the holding time is 1-2h, and the heating rate is 3-10℃ / min.
[0019] A carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material is disclosed. The composite electrode material includes hierarchical porous carbon microspheres and carbon nanotubes bridging the surface and between the microspheres. The hierarchical porous carbon microspheres provide ion adsorption sites and mass transfer channels, while the carbon nanotubes construct an electron conduction network.
[0020] Furthermore, the hierarchical porous carbon microspheres have a pore structure in which micropores and mesopores are distributed in a coordinated manner, and the pore structure extends through the spherical carbon skeleton.
[0021] An application of a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material in capacitive deionization is disclosed. The composite electrode material is used for ion removal in saline systems, wherein the saline system is one or a mixture of brackish water, simulated brine, and industrial saline wastewater. The capacitive deionization operates at a voltage of 0.8-1.6V, and the ion is Na+. + Cl - Mg 2+ Ca 2+ One or more of them are mixed together.
[0022] The advantages of this invention over the prior art are:
[0023] 1. This invention uses hierarchical porous carbon microspheres as the main adsorption framework of a composite material, possessing a high specific surface area and a pore structure with a synergistic distribution of micropores and mesopores. The micropores provide numerous ion adsorption sites, enhancing the material's electroadsorption capacity; the mesopores facilitate electrolyte penetration and rapid ion diffusion, reducing mass transfer resistance. This synergistic effect helps to balance adsorption capacity and adsorption rate, thus providing a sound structural basis for efficient ion removal in capacitive deionization processes.
[0024] 2. This invention introduces carbon nanotubes as a bridging conductive component into hierarchical porous carbon microspheres, enabling the construction of a relatively continuous electronic conduction network on and between the microspheres. Compared with using carbon microspheres alone, this structure effectively reduces interparticle contact resistance, shortens electron migration paths, improves the overall conductivity of the composite material, and enhances the electron transport efficiency and rate response capability of the electrode during capacitive deionization, thus contributing to improved overall desalination performance.
[0025] 3. This invention pre-treats carbon nanotubes with oxidation, introducing oxygen-containing functional groups such as carboxyl and / or hydroxyl groups onto their surface. This significantly improves the dispersion performance of carbon nanotubes in liquid systems and their interfacial compatibility with hierarchical porous carbon microspheres. The pre-treated carbon nanotubes are more easily and uniformly distributed on the surface and between the microspheres, thereby improving the uniformity and effectiveness of the conductive network construction and further enhancing the utilization rate of active sites and ion transport efficiency in the composite system.
[0026] 4. This invention adopts a technical route of "carbon nanotube pretreatment—mixing and composite—secondary heat treatment," which, compared to simple mechanical mixing, can further enhance the interfacial bonding between carbon nanotubes and hierarchical porous carbon microspheres. Secondary heat treatment helps improve the contact state and structural integrity between components, reducing the detachment, aggregation, or localized failure of carbon nanotubes during use, thereby improving the overall structural stability, cycle durability, and long-term reliability of the composite material.
[0027] 5. The preparation method of this invention has clear steps and a reasonable process route. The composite electrode material can be prepared mainly through hierarchical porous carbon microsphere construction, carbon nanotube pretreatment, mixing and compounding, and secondary heat treatment. The conditions are easy to control and the repeatability is good. The obtained material is not only suitable for capacitive deionization treatment of brackish water and simulated brine, but also for ion removal in industrial saline wastewater and other saline systems, demonstrating good application scalability and practical promotion value.
[0028] In summary, this invention constructs a composite electrode material that combines a hierarchical pore structure, a continuous conductive network, and good interfacial stability by compositing treated carbon nanotubes with hierarchical porous carbon microspheres and performing secondary heat treatment. This material can effectively improve the ion removal efficiency, mass transfer performance, and cycle stability during capacitive deionization. Attached Figure Description
[0029] Figure 1 is a nitrogen adsorption-desorption isotherm diagram of the composite electrode material prepared in Example 1.
[0030] Figure 2 is a pore size distribution diagram of the composite electrode material prepared in Example 1.
[0031] Figure 3 is a nitrogen adsorption-desorption isotherm diagram of the composite electrode material prepared in Example 2.
[0032] Figure 4 is a pore size distribution diagram of the composite electrode material prepared in Example 2.
[0033] Figure 5 is a nitrogen adsorption-desorption isotherm diagram of the composite electrode material prepared in Example 3.
[0034] Figure 6 is a pore size distribution diagram of the composite electrode material prepared in Example 3.
[0035] Figure 7 is a cyclic voltammetry curve of the composite electrode material prepared in Example 1 at a scan rate of 5 mV / s.
[0036] Figure 8 is a constant current charge-discharge curve of the composite electrode material prepared in Example 1 at a current density of 0.5 A / g. Detailed Implementation
[0037] The specific embodiments of the present invention will now be described in detail with reference to the accompanying drawings. However, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] Specific Implementation Method 1: This implementation method provides a method for preparing a pretreated carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, including the following steps:
[0039] S1. A spherical precursor is prepared by mixing a carbon source, a heteroatom source, and a nano-silica template in a dispersion medium and then using a hydrothermal reaction method.
[0040] Further, the carbon source is one or more of sugars, cellulose, furfural, phenolic resins, and water-soluble polymeric carbon sources; preferably, the carbon source is one or more of glucose, sucrose, starch, cellulose, furfural, polyvinyl alcohol, phenolic resin, and resorcinol-formaldehyde resin. The heteroatom source is one or more of boron-containing compounds and nitrogen-containing compounds; preferably, the heteroatom source is one or more of boric acid, borax, borate esters, melamine, urea, ammonia, polypyrrole, and polyacrylonitrile. The dispersion medium is one or more of deionized water, ethanol, and isopropanol.
[0041] Furthermore, the mass ratio of the carbon source, heteroatom source, and nano-silica template is (20-50):(10-50):(0.5-3), the mass ratio of the carbon source to the dispersion medium is (5-15):(50-100), and the hydrothermal reaction temperature is 160-200℃, with a time of 6-12h.
[0042] S2. The spherical precursor obtained in step S1 is subjected to high-temperature carbonization, acid washing to remove the template, and activation to create pores, in order to prepare fractional porous carbon microspheres.
[0043] Furthermore, the spherical precursor is subjected to high-temperature carbonization in an inert atmosphere, wherein the inert atmosphere is one or a mixture of nitrogen, argon, and helium, the carbonization temperature is 900-1100℃, and the holding time is 1-3 h. This high-temperature carbonization is the first stage of heat treatment.
[0044] Furthermore, the acid etching process removes the silica template using an acid solution, preferably hydrofluoric acid. After acid etching, the resulting product is washed until neutral and dried to obtain porous carbon microspheres with the template removed.
[0045] Furthermore, the activated pore-forming process is in N 2 / The activation process was carried out under a CO2 mixed atmosphere at a temperature of 700-900℃ for 0.5-2 h to obtain a hierarchical porous carbon microsphere structure with a synergistic distribution of micropores and mesopores. CO2 comprised 5%-60% of the total volume of the N2 / CO2 mixed gas, and the mixed gas flow rate was 50-500 mL / min.
[0046] S3. After carbon nanotubes undergo oxidation pretreatment, they are dispersed in a dispersion medium and then mixed and composited with the hierarchical porous carbon microspheres obtained in step S2 to obtain a composite precursor.
[0047] Furthermore, the carbon nanotube oxidation pretreatment is carried out using one or more of the following methods: nitric acid treatment, sulfuric acid / nitric acid mixed acid treatment, and hydrogen peroxide treatment. When using sulfuric acid / nitric acid mixed acid treatment, the volume ratio of sulfuric acid to nitric acid is (1-3):1. The treatment temperature is 40-80℃, and the treatment time is 1-6 h. The dispersion medium is one or more of the following: deionized water, ethanol, and isopropanol.
[0048] Furthermore, the mass ratio of the hierarchical porous carbon microspheres to the pre-oxidized carbon nanotubes is 100:1-2:1, preferably 20:1-5:1. The mixing and compounding conditions are: stirring at room temperature to 60°C for 1-12 h, followed by ultrasonic treatment for 5-60 min.
[0049] S4. After drying the composite precursor obtained in step S3, perform a second heat treatment under an inert atmosphere to obtain a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material.
[0050] Furthermore, the drying temperature is 50-90℃, and the drying time is 6-24 h. The second stage of heat treatment is carried out under a nitrogen or argon atmosphere, with a heat treatment temperature of 700-900℃, a holding time of 1-2 h, and a heating rate of 3-10℃ / min.
[0051] In this embodiment, the second heat treatment refers to a further heat treatment of the composite precursor after the first heat treatment in step S2. This second heat treatment further enhances the interfacial bonding between carbon nanotubes and hierarchical porous carbon microspheres, improving the continuity and structural stability of the overall conductive network of the composite material.
[0052] Specific Implementation Method Two: This implementation method provides a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material prepared by the method described in Specific Implementation Method One. The composite electrode material includes hierarchical porous carbon microspheres and carbon nanotubes bridging the surface of the microspheres and between the microspheres. The hierarchical porous carbon microspheres provide ion adsorption sites and mass transfer channels, while the carbon nanotubes construct an electron conduction network.
[0053] Furthermore, the hierarchical porous carbon microspheres possess a pore structure with a synergistic distribution of micropores and mesopores, and the pore structure extends throughout the spherical carbon framework. Micropores provide ion adsorption sites, while mesopores promote electrolyte wetting and ion diffusion; the synergy of these two features is beneficial for improving the adsorption capacity and mass transfer efficiency during the capacitor deionization process.
[0054] Furthermore, the oxidized carbon nanotubes can form bridging conductive structures on the surface of hierarchical porous carbon microspheres and between the microspheres. This structure helps to reduce the contact resistance between hierarchical porous carbon microspheres, shorten the electron transport path, and improve the electron transport capability and structural stability of the composite electrode material.
[0055] Furthermore, after the second heat treatment, the interfacial bonding between the carbon nanotubes and the hierarchical porous carbon microspheres is further enhanced, improving the continuity of the conductive network and the cycling stability of the composite material. Therefore, the composite electrode material possesses a hierarchical pore structure, an electronic conduction network, and a stable composite interface, making it suitable for use as a capacitive deionization electrode material.
[0056] Specific Implementation Method 3: This implementation method provides an application of a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material in capacitive deionization. The composite electrode material is used for ion removal in a saline system. The saline system is one or more of brackish water, simulated brine, and industrial saline wastewater. The capacitive deionization operating voltage is 0.8–1.6 V, and the ion is Na+. + Cl - Mg 2+ Ca 2+ One or more of them are mixed together.
[0057] In the capacitor deionization process, the microporous structure in the hierarchical porous carbon microspheres can provide adsorption sites for ions, while the mesoporous structure can promote the entry of electrolyte into the electrode and accelerate ion diffusion. Carbon nanotubes form a bridging conductive network between the hierarchical porous carbon microspheres, which is beneficial to improving electron transport efficiency and reducing electrode polarization. The second heat treatment enhances the interfacial bonding between carbon nanotubes and hierarchical porous carbon microspheres, which helps to improve the structural stability of the composite electrode material during charge-discharge cycles.
[0058] Therefore, when the composite electrode material is used for capacitive deionization, it can improve the ion removal efficiency, mass transfer performance and cycle stability in saline systems.
[0059] Example 1
[0060] This embodiment provides a method for preparing a pretreated carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, including the following steps:
[0061] S1. Raw material mixing and precursor solution preparation
[0062] Weigh 2.0 g of glucose, 0.5 g of boric acid, and 0.8 g of melamine, add them to 50 mL of deionized water, and stir magnetically for 1 h at room temperature to ensure thorough mixing of all components, thus obtaining a precursor mixture solution. Glucose serves as the carbon source, while boric acid and melamine serve as heteroatom sources.
[0063] S2, Hydrothermal preparation of spherical precursors
[0064] The precursor mixture obtained in step S1 was thoroughly mixed with 1.5 g of nano-SiO2, and then the mixture was transferred to a 100 mL hydrothermal reactor and hydrothermally treated at 180 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain a brown liquid. The product was washed alternately with deionized water and anhydrous ethanol until no obvious particulate impurities were found, and then dried in an oven at 60 °C for 12 h to obtain a mixture of brown solid powders.
[0065] S3, High-temperature carbonization treatment
[0066] The brown solid powder mixture obtained in step S2 was transferred to a tube furnace and heated to 1000℃ at a heating rate of 5℃ / min under N2 atmosphere protection, and carbonized for 2 h. After carbonization, it was naturally cooled to room temperature to obtain a carbonized sample. The high-temperature carbonization was the first heat treatment.
[0067] S4, Template Etching and Removal
[0068] The carbonized sample obtained in step S3 was mixed with 10 wt% hydrofluoric acid and etched at room temperature for 12 h to remove the SiO2 template. After etching, the resulting product was repeatedly washed until neutral and then dried at 60°C for 12 h to obtain porous carbon microspheres without the template.
[0069] S5. Activation and pore-forming process to prepare hierarchical porous carbon microspheres
[0070] The porous carbon microspheres obtained in step S4 were transferred back to a tube furnace and activated for 1 h at a heating rate of 5 °C / min under a N2 / CO2 mixed atmosphere (N2 to CO2 volume ratio of 4:1, mixed gas volume flow rate of 100 mL / min). After activation, the tube furnace was naturally cooled to room temperature to obtain hierarchical porous carbon microspheres.
[0071] S6, Carbon nanotube oxidation pretreatment
[0072] Weigh 0.20 g of multi-walled carbon nanotubes and add them to 80 mL of a 3:1 mixture of concentrated sulfuric acid and concentrated nitric acid. Stir the mixture magnetically at 60 °C for 2 h. After the reaction is complete, allow it to cool naturally and slowly pour the resulting mixture into a large amount of deionized water. Filter the mixture and wash it repeatedly with deionized water until the filtrate is neutral. Then, place the sample in a vacuum drying oven at 60 °C and dry it for 12 h to obtain the treated carbon nanotubes.
[0073] S7, Preparation of Composite Precursors
[0074] Weigh 0.10 g of the treated carbon nanotubes obtained in step S6 and add them to 50 mL of an ethanol / deionized water mixed solution, wherein the volume ratio of ethanol to deionized water is 4:1. Disperse the solution under ultrasonic conditions for 60 min to obtain a carbon nanotube dispersion. Separately weigh 1.00 g of the hierarchical porous carbon microspheres obtained in step S5 and add them to 100 mL of an ethanol / deionized water mixed solution. First, disperse the solution under ultrasonic conditions for 20 min to obtain a hierarchical porous carbon microsphere suspension. Then, slowly add the carbon nanotube dispersion dropwise to the hierarchical porous carbon microsphere suspension, stir magnetically at room temperature for 4 h, and continue to sonicate for 20 min to obtain a composite suspension. Separate the composite suspension by vacuum filtration, collect the obtained solid product, and dry it in a vacuum drying oven at 60 °C for 12 h to obtain the composite precursor.
[0075] S8, Second Stage Heat Treatment
[0076] The composite precursor obtained in step S7 was placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under N2 atmosphere protection. The temperature was held for 2 h and then naturally cooled to room temperature to obtain a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, denoted as CNT / CMS-1.
[0077] As shown in Figure 1, the composite electrode material prepared in Example 1 exhibits obvious nitrogen adsorption-desorption behavior. The adsorption amount increases rapidly in the low relative pressure region, indicating the presence of a certain number of microporous structures in the material. The adsorption amount continues to increase in the higher relative pressure region, indicating the presence of mesopores or larger mass transfer channels in the material. These results demonstrate that the composite electrode material obtained in Example 1 possesses a hierarchical pore structure with a synergistic distribution of micropores and mesopores, which is beneficial for simultaneously providing ion adsorption sites and ion diffusion channels during capacitor deionization.
[0078] As shown in Figure 2, the composite electrode material prepared in Example 1 exhibits a distinct pore size distribution, with the pore size mainly distributed within the micropore and mesopore range. This pore size distribution corroborates the nitrogen adsorption-desorption results in Figure 1, indicating that after template etching and CO2 activation treatment, the material forms a relatively rich hierarchical pore structure. This structure is beneficial for improving electrolyte wettability and salt ion transport efficiency.
[0079] As shown in Figure 7, the composite electrode material prepared in Example 1 exhibits a clear capacitive response characteristic in its cyclic voltammetry curve at a scan rate of 5 mV / s. The curve shows good closure, indicating that the material has good reversibility and charge response capability during electrochemical charge-discharge processes. This result suggests that the introduction of carbon nanotubes is beneficial to improving the electron transport performance of the composite material.
[0080] As shown in Figure 8, the composite electrode material prepared in Example 1 exhibits relatively stable charge-discharge behavior under a constant current charge-discharge curve at a current density of 0.5 A / g, indicating that the material possesses good capacitance energy storage characteristics and charge-discharge reversibility. This result further demonstrates that the composite electrode material has the potential to be used as a capacitive deionization electrode material.
[0081] Example 2
[0082] This embodiment provides a method for preparing a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, comprising the following steps:
[0083] S1. Raw material mixing and precursor solution preparation
[0084] Weigh 2.0 g glucose, 0.5 g boric acid and 0.8 g melamine, add them to 50 mL deionized water, and stir magnetically at room temperature for 1 h to ensure that the components are fully mixed and homogeneous, thus obtaining a precursor mixed solution.
[0085] S2, Hydrothermal preparation of spherical precursors
[0086] The precursor mixture obtained in step S1 was thoroughly mixed with 1.5 g of nano-SiO2, and then the mixture was transferred to a 100 mL hydrothermal reactor and hydrothermally treated at 180 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain a brown liquid. The product was washed alternately with deionized water and anhydrous ethanol until no obvious particulate impurities were found, and then dried in an oven at 60 °C for 12 h to obtain a brown solid powder mixture.
[0087] S3, High-temperature carbonization treatment
[0088] The brown solid powder mixture obtained in step S2 was transferred to a tube furnace and heated to 1000°C at a heating rate of 5°C / min under N2 atmosphere protection, and carbonized for 2 h. After carbonization, it was naturally cooled to room temperature to obtain a carbonized sample. The high-temperature carbonization was the first heat treatment.
[0089] S4, Template Etching and Removal
[0090] The carbonized sample obtained in step S3 was mixed with 10 wt% hydrofluoric acid and etched by stirring at room temperature for 12 h. After etching, the resulting product was repeatedly washed until neutral and then dried at 60℃ for 12 h to obtain porous carbon microspheres after template removal.
[0091] S5. Activation and pore-forming process to prepare hierarchical porous carbon microspheres
[0092] The porous carbon microspheres obtained in step S4 were transferred to a tube furnace again and heated to 800°C at a heating rate of 5°C / min under a N2 / CO2 mixed atmosphere for 1 h. After activation, the microspheres were naturally cooled to room temperature to obtain hierarchical porous carbon microspheres.
[0093] S6, Carbon nanotube oxidation pretreatment
[0094] Weigh 0.20 g of multi-walled carbon nanotubes and add them to 80 mL of a 3:1 mixture of concentrated sulfuric acid and concentrated nitric acid. Stir the mixture magnetically at 60 °C for 2 h. After the reaction is complete, allow it to cool naturally and slowly pour the resulting mixture into a large amount of deionized water. Filter the mixture and wash it repeatedly with deionized water until the filtrate is neutral. Then, place the sample in a vacuum drying oven at 60 °C and dry it for 12 h to obtain the treated carbon nanotubes.
[0095] S7, Preparation of Composite Precursors
[0096] Weigh 0.20 g of the treated carbon nanotubes obtained in step S6 and add them to 50 mL of an ethanol / deionized water mixed solution, wherein the volume ratio of ethanol to deionized water is 4:1. Disperse the solution under ultrasonic conditions for 60 min to obtain a carbon nanotube dispersion. Separately weigh 1.00 g of the hierarchical porous carbon microspheres obtained in step S5 and add them to 100 mL of an ethanol / deionized water mixed solution. First, disperse the solution under ultrasonic conditions for 20 min to obtain a hierarchical porous carbon microsphere suspension. Then, slowly add the carbon nanotube dispersion dropwise to the hierarchical porous carbon microsphere suspension, stir magnetically at room temperature for 4 h, and continue to sonicate for 20 min to obtain a composite suspension. Separate the composite suspension by vacuum filtration, collect the obtained solid product, and dry it in a vacuum drying oven at 60 °C for 12 h to obtain the composite precursor.
[0097] S8, Second Stage Heat Treatment
[0098] The composite precursor obtained in step S7 was placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under N2 atmosphere protection. The temperature was held for 2 h and then naturally cooled to room temperature to obtain a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, denoted as CNT / CMS-2.
[0099] As shown in Figure 3, the composite electrode material prepared in Example 2 also exhibits significant nitrogen adsorption-desorption behavior, indicating that the material maintains a good porous structure. Compared with Example 1, the amount of carbon nanotubes added in Example 2 is higher, yet a certain pore structure is still maintained, indicating that the introduction of carbon nanotubes does not completely block the pores of the hierarchical porous carbon microspheres, which is beneficial for maintaining ion adsorption and mass transfer performance.
[0100] As shown in Figure 4, the composite electrode material prepared in Example 2 exhibits pore size distribution characteristics within the micropore and mesopore ranges, indicating that the material still possesses a hierarchical pore structure suitable for ion adsorption and diffusion. This structure, combined with the carbon nanotube conductive network, is beneficial for improving the electron transport capability of the composite electrode material and the ion migration efficiency during the capacitor deionization process.
[0101] Example 3
[0102] This embodiment provides a method for preparing a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, comprising the following steps:
[0103] S1. Raw material mixing and precursor solution preparation
[0104] Weigh 2.0 g glucose, 0.5 g boric acid and 0.8 g melamine, add them to 50 mL deionized water, and stir magnetically at room temperature for 1 h to ensure that the components are fully mixed and homogeneous, thus obtaining a precursor mixed solution.
[0105] S2, Hydrothermal preparation of spherical precursors
[0106] The precursor mixture obtained in step S1 was thoroughly mixed with 1.5 g of nano-SiO2, and then the mixture was transferred to a 100 mL hydrothermal reactor and hydrothermally treated at 180 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain a brown liquid. The product was washed alternately with deionized water and anhydrous ethanol until no obvious particulate impurities were found, and then dried in an oven at 60 °C for 12 h to obtain a mixture of brown solid powders.
[0107] S3, High-temperature carbonization treatment
[0108] The brown solid powder mixture obtained in step S2 was transferred to a tube furnace and heated to 1000°C at a heating rate of 5°C / min under N2 atmosphere protection, and carbonized for 2 h. After carbonization, it was naturally cooled to room temperature to obtain a carbonized sample. The high-temperature carbonization was the first heat treatment.
[0109] S4, Template Etching and Removal
[0110] The carbonized sample obtained in step S3 was mixed with 10 wt% hydrofluoric acid and etched by stirring at room temperature for 12 h. After etching, the resulting product was repeatedly washed until neutral and then dried at 60℃ for 12 h to obtain porous carbon microspheres after template removal.
[0111] S5. Activation and pore-forming process to prepare hierarchical porous carbon microspheres
[0112] The porous carbon microspheres obtained in step S4 were transferred to a tube furnace again and heated to 800°C at a heating rate of 5°C / min under a N2 / CO2 mixed atmosphere for 1 h. After activation, the microspheres were naturally cooled to room temperature to obtain hierarchical porous carbon microspheres.
[0113] S6, Carbon nanotube oxidation pretreatment
[0114] Weigh 0.20 g of multi-walled carbon nanotubes and add them to 80 mL of a 3:1 mixture of concentrated sulfuric acid and concentrated nitric acid. Stir the mixture magnetically at 60 °C for 2 h. After the reaction is complete, allow it to cool naturally and slowly pour the resulting mixture into a large amount of deionized water. Filter the mixture and wash it repeatedly with deionized water until the filtrate is neutral. Then, place the sample in a vacuum drying oven at 60 °C and dry it for 12 h to obtain the treated carbon nanotubes.
[0115] S7, Preparation of Composite Precursors
[0116] Weigh 0.05 g of the treated carbon nanotubes obtained in step S6 and add them to 50 mL of an ethanol / deionized water mixed solution, wherein the volume ratio of ethanol to deionized water is 4:1. Disperse the solution under ultrasonic conditions for 60 min to obtain a carbon nanotube dispersion. Separately weigh 1.00 g of the hierarchical porous carbon microspheres obtained in step S5 and add them to 100 mL of an ethanol / deionized water mixed solution. First, disperse the solution under ultrasonic conditions for 20 min to obtain a hierarchical porous carbon microsphere suspension. Then, slowly add the carbon nanotube dispersion dropwise to the hierarchical porous carbon microsphere suspension, stir magnetically at room temperature for 4 h, and continue to sonicate for 20 min to obtain a composite suspension. Separate the composite suspension by vacuum filtration, collect the obtained solid product, and dry it in a vacuum drying oven at 60 °C for 12 h to obtain the composite precursor.
[0117] S8, Secondary Heat Treatment
[0118] The composite precursor obtained in step S7 was placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under N2 atmosphere protection. The temperature was held for 2 h and then naturally cooled to room temperature to obtain a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, denoted as CNT / CMS-3.
[0119] As shown in Figure 5, the composite electrode material prepared in Example 3 exhibits nitrogen adsorption-desorption characteristics, indicating that a certain pore structure still exists in the material. Compared with Examples 1 and 2, the amount of carbon nanotubes added in Example 3 is lower, and the pore structure contribution of hierarchical porous carbon microspheres in the composite system is more significant, which is beneficial for maintaining ion adsorption sites and mass transfer channels.
[0120] As shown in Figure 6, the composite electrode material prepared in Example 3 exhibits a certain pore size distribution, with the pore size mainly distributed within the micropore and mesopore range. This result indicates that even with a low carbon nanotube addition, the composite electrode material still maintains a hierarchical pore structure, which is beneficial for electrolyte wetting and salt ion diffusion.
[0121] Comparative Example 1
[0122] A method for preparing hierarchical porous carbon microspheres includes the following steps:
[0123] S1. Raw material mixing and precursor solution preparation
[0124] Weigh 2.0 g glucose, 0.5 g boric acid and 0.8 g melamine, add them to 50 mL deionized water, and stir magnetically at room temperature for 1 h to ensure that the components are fully mixed and homogeneous, thus obtaining a precursor mixed solution.
[0125] S2, Hydrothermal preparation of spherical precursors
[0126] The precursor mixture obtained in step S1 was thoroughly mixed with 1.5 g of nano-SiO2, and then the mixture was transferred to a 100 mL hydrothermal reactor and hydrothermally treated at 180 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain a brown liquid. The product was washed alternately with deionized water and anhydrous ethanol until no obvious particulate impurities were found, and then dried in an oven at 60 °C for 12 h to obtain a brown solid powder mixture.
[0127] S3, High-temperature carbonization treatment
[0128] The brown solid powder mixture obtained in step S2 was transferred to a tube furnace and heated to 1000°C at a heating rate of 5°C / min under N2 atmosphere protection, and carbonized for 2 h. After carbonization, it was naturally cooled to room temperature to obtain the carbonized sample.
[0129] S4, Template Etching and Removal
[0130] The carbonized sample obtained in step S3 was mixed with 10 wt% hydrofluoric acid and etched by stirring at room temperature for 12 h. After etching, the resulting product was repeatedly washed until neutral and then dried at 60°C for 12 h to obtain porous carbon microspheres after removing the template.
[0131] S5. Activation and pore-forming process to prepare hierarchical porous carbon microspheres
[0132] The porous carbon microspheres obtained in step S4 were transferred to a tube furnace again and heated to 800°C at a heating rate of 5°C / min under a N2 / CO2 mixed atmosphere (N2 to CO2 volume ratio of 4:1, mixed gas volume flow rate of 100 mL / min) for 1 h. After activation, the microspheres were naturally cooled to room temperature to obtain hierarchical porous carbon microspheres, denoted as CMS.
[0133] Compared to Comparative Example 1, Example 1 further introduces pre-oxidized carbon nanotubes into hierarchical porous carbon microspheres, and constructs a carbon nanotube bridging conductive network through hybridization and a second-stage heat treatment. The hierarchical porous carbon microspheres provide ion adsorption sites and micropore-mesopore synergistic mass transfer channels, while the carbon nanotubes form continuous electron conduction paths on the surface and between the microspheres, thereby reducing interparticle contact resistance and improving the electron transport efficiency, ion diffusion efficiency, and electrochemical response capability of the composite electrode material. The second-stage heat treatment also enhances the interfacial bonding between the carbon nanotubes and the hierarchical porous carbon microspheres, improving the structural stability and cycle durability of the material during capacitive deionization.
[0134] Comparative Example 1 only prepared hierarchical porous carbon microspheres without introducing carbon nanotubes to construct a bridging conductive network or forming a composite interface between carbon nanotubes and carbon microspheres. Although it has a certain hierarchical pore structure and ion adsorption capacity, the electron transport path between microspheres is relatively discontinuous, and the contact resistance between particles is relatively large. In the process of capacitive deionization, problems such as insufficient electron transport efficiency, limited rate response capability, and insufficient long-cycle stability are prone to occur.
[0135] Comparative Example 2
[0136] A method for preparing an untreated carbon nanotube / hierarchical porous carbon microsphere composite material includes the following steps:
[0137] S1. Raw material mixing and precursor solution preparation
[0138] Weigh 2.0 g glucose, 0.5 g boric acid and 0.8 g melamine, add them to 50 mL deionized water, and stir magnetically at room temperature for 1 h to ensure that the components are fully mixed and homogeneous, thus obtaining a precursor mixed solution.
[0139] S2, Hydrothermal preparation of spherical precursors
[0140] The precursor mixture obtained in step S1 was thoroughly mixed with 1.5 g of nano-SiO2, and then the mixture was transferred to a 100 mL hydrothermal reactor and hydrothermally treated at 180 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain a brown liquid. The product was washed alternately with deionized water and anhydrous ethanol until no obvious particulate impurities were found, and then dried in an oven at 60 °C for 12 h to obtain a mixture of brown solid powders.
[0141] S3, High-temperature carbonization treatment
[0142] The brown solid powder mixture obtained in step S2 was transferred to a tube furnace and heated to 1000°C at a heating rate of 5°C / min under N2 atmosphere protection, and carbonized for 2 h. After carbonization, it was naturally cooled to room temperature to obtain the carbonized sample.
[0143] S4, Template Etching and Removal
[0144] The carbonized sample obtained in step S3 was mixed with 10 wt% hydrofluoric acid and etched by stirring at room temperature for 12 h. After etching, the resulting product was repeatedly washed until neutral and then dried at 60°C for 12 h to obtain porous carbon microspheres after removing the template.
[0145] S5. Activation and pore-forming process to prepare hierarchical porous carbon microspheres
[0146] The porous carbon microspheres obtained in step S4 were transferred to a tube furnace again and heated to 800°C at a heating rate of 5°C / min under a N2 / CO2 mixed atmosphere for 1 h. After activation, the microspheres were naturally cooled to room temperature to obtain hierarchical porous carbon microspheres.
[0147] S6, Untreated carbon nanotube dispersion
[0148] Weigh 0.10 g of untreated multi-walled carbon nanotubes and add them to 50 mL of ethanol / deionized water mixed solution, wherein the volume ratio of ethanol to deionized water is 4:1. Disperse under ultrasonic conditions for 60 min to obtain an untreated carbon nanotube dispersion.
[0149] S7, Preparation of Composite Precursors
[0150] Weigh 1.00 g of the hierarchical porous carbon microspheres obtained in step S5 and add them to 100 mL of ethanol / deionized water mixed solution. First, ultrasonically disperse them for 20 min. Then, slowly add the untreated carbon nanotube dispersion obtained in step S6 to the hierarchical porous carbon microsphere suspension. Stir magnetically at room temperature for 4 h and continue ultrasonication for 20 min to obtain a composite suspension. Separate the composite suspension by vacuum filtration, collect the obtained solid product, and dry it in a vacuum drying oven at 60℃ for 12 h to obtain the composite precursor.
[0151] S8, Secondary Heat Treatment
[0152] The composite precursor obtained in step S7 was placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under N2 atmosphere protection. The temperature was held for 2 h and then naturally cooled to room temperature to obtain an untreated carbon nanotube / hierarchical porous carbon microsphere composite material, denoted as uCNT / CMS.
[0153] Example 2, compared to Comparative Example 2, uses pre-treated carbon nanotubes combined with hierarchical porous carbon microspheres. Oxidation pretreatment introduces oxygen-containing functional groups such as carboxyl and hydroxyl groups onto the surface of the carbon nanotubes, improving their dispersibility in the dispersion medium and enhancing their interfacial compatibility with the hierarchical porous carbon microspheres. The pre-treated carbon nanotubes are more easily and uniformly distributed on the surface and between the microspheres, facilitating the formation of a stable and continuous bridging conductive network, thereby improving the electron transport efficiency, interfacial stability, and recyclability of the composite electrode material.
[0154] Comparative Example 2 uses untreated carbon nanotubes combined with hierarchical porous carbon microspheres. The untreated carbon nanotubes have weak surface polarity, making them prone to aggregation in the liquid phase and hindering the uniform bridging of the hierarchical porous carbon microspheres. Furthermore, the interfacial bonding between the untreated nanotubes and the carbon microspheres is weak, easily leading to discontinuities or localized failures in the conductive network. Therefore, Comparative Example 2 may suffer from problems such as unstable electron transport paths, insufficient interfacial bonding, limited ion mass transfer efficiency, and poor cycle stability during capacitive deionization.
[0155] Comparative Example 3
[0156] A method for preparing a carbon nanotube / hierarchical porous carbon microsphere composite material without secondary heat treatment includes the following steps:
[0157] S1. Raw material mixing and precursor solution preparation
[0158] Weigh 2.0 g glucose, 0.5 g boric acid and 0.8 g melamine, add them to 50 mL deionized water, and stir magnetically at room temperature for 1 h to ensure that the components are fully mixed and homogeneous, thus obtaining a precursor mixed solution.
[0159] S2, Hydrothermal preparation of spherical precursors
[0160] The precursor mixture obtained in step S1 was thoroughly mixed with 1.5 g of nano-SiO2, and then the mixture was transferred to a 100 mL hydrothermal reactor and hydrothermally treated at 180 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain a brown liquid. The product was washed alternately with deionized water and anhydrous ethanol until no obvious particulate impurities were found, and then dried in an oven at 60 °C for 12 h to obtain a brown solid powder mixture.
[0161] S3, High-temperature carbonization treatment
[0162] The brown solid powder mixture obtained in step S2 was transferred to a tube furnace and heated to 1000°C at a heating rate of 5°C / min under N2 atmosphere protection, and carbonized for 2 h. After carbonization, it was naturally cooled to room temperature to obtain the carbonized sample.
[0163] S4, Template Etching and Removal
[0164] The carbonized sample obtained in step S3 was mixed with 10 wt% hydrofluoric acid and etched by stirring at room temperature for 12 h. After etching, the resulting product was repeatedly washed until neutral and then dried at 60℃ for 12 h to obtain porous carbon microspheres after template removal.
[0165] S5. Activation and pore-forming process to prepare hierarchical porous carbon microspheres
[0166] The porous carbon microspheres obtained in step S4 were transferred back to a tube furnace and activated for 1 h at a heating rate of 5 °C / min under a N2 / CO2 mixed atmosphere, reaching 800 °C. After activation, the microspheres were allowed to cool naturally to room temperature to obtain hierarchical porous carbon microspheres.
[0167] S6, Carbon nanotube oxidation pretreatment
[0168] Weigh 0.20 g of multi-walled carbon nanotubes and add them to 80 mL of a 3:1 mixture of concentrated sulfuric acid and concentrated nitric acid. Stir the mixture magnetically at 60 °C for 2 h. After the reaction is complete, allow it to cool naturally and slowly pour the resulting mixture into a large amount of deionized water. Filter the mixture and wash it repeatedly with deionized water until the filtrate is neutral. Then, place the sample in a vacuum drying oven at 60 °C and dry it for 12 h to obtain the treated carbon nanotubes.
[0169] S7, Preparation of Composite Precursors
[0170] Weigh 0.10 g of the treated carbon nanotubes obtained in step S6 and add them to 50 mL of an ethanol / deionized water mixed solution, wherein the volume ratio of ethanol to deionized water is 4:1. Disperse the solution under ultrasonic conditions for 60 min to obtain a carbon nanotube dispersion. Separately weigh 1.00 g of the hierarchical porous carbon microspheres obtained in step S5 and add them to 100 mL of an ethanol / deionized water mixed solution. Disperse the solution under ultrasonic conditions for 20 min. Then, slowly add the carbon nanotube dispersion dropwise to the hierarchical porous carbon microsphere suspension, stir magnetically at room temperature for 4 h, and continue ultrasonication for 20 min to obtain a composite suspension. Separate the composite suspension by vacuum filtration, collect the obtained solid product, and dry it in a vacuum drying oven at 60℃ for 12 h to obtain the composite precursor, denoted as CNT / CMS-P.
[0171] Compared to Comparative Example 3, Example 3 underwent a second heat treatment after the composite precursor was prepared. This second heat treatment improved the contact state between carbon nanotubes and hierarchical porous carbon microspheres, enhanced the interfacial bonding between them, and improved the continuity and structural stability of the conductive network in the composite material. Through this treatment, carbon nanotubes can more stably bridge the hierarchical porous carbon microspheres, thereby improving the electron transport efficiency and cycle durability of the composite electrode material during capacitive deionization.
[0172] Comparative Example 3, without a second heat treatment, yielded only a carbon nanotube / hierarchical porous carbon microsphere composite precursor. Due to the lack of subsequent heat treatment reinforcement, the interaction between the carbon nanotubes and the hierarchical porous carbon microspheres primarily relied on physical mixing or weak interfacial interactions, resulting in insufficient composite interface stability and poor continuity of the conductive network. During capacitive deionization, carbon nanotubes may experience localized detachment, aggregation, or interruption of conductive pathways, thereby affecting the material's electron transport efficiency, structural stability, and recyclability.
[0173] The preparation method of this invention involves preparing hierarchical porous carbon microspheres according to existing methods; pre-treating carbon nanotubes with oxidation; dispersing the treated carbon nanotubes in a dispersion medium and mixing them with the hierarchical porous carbon microspheres to obtain a composite precursor; drying the obtained composite precursor and then subjecting it to a secondary heat treatment under an inert atmosphere to obtain a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material. The hierarchical porous carbon microspheres provide a high specific surface area and micropore-mesopore synergistic mass transfer channels. The carbon nanotubes construct a conductive bridging network between the microspheres. The secondary heat treatment further enhances interfacial bonding and overall conductivity, thereby improving electron transport efficiency, ion diffusion rate, and capacitive deionization performance. This method is suitable for ion removal in brackish water, simulated brine, industrial saline wastewater, and other saline systems.
Claims
1. A method for preparing a pretreated carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material, characterized in that: Includes the following steps: S1. A spherical precursor was prepared by mixing a carbon source, a heteroatom source and a nano-silica template in a dispersion medium and using a hydrothermal reaction method. S2. The spherical precursor obtained in step S1 is subjected to high-temperature carbonization, acid washing to remove the template, and activation to create pores, thereby producing fractional porous carbon microspheres; wherein, the high-temperature carbonization is the first stage of heat treatment. S3. Carbon nanotubes are pretreated by oxidation and then dispersed in a dispersion medium. They are then mixed and composited with the hierarchical porous carbon microspheres obtained in step S2 to obtain a composite precursor. S4. After drying the composite precursor obtained in step S3, perform a second heat treatment under an inert atmosphere to obtain a carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material.
2. The preparation method according to claim 1, characterized in that: In step S1, the carbon source is one or more of the following: sugars, cellulose, furfural, phenolic compounds, and water-soluble polymeric carbon sources. The heteroatom source is one or more of boron-containing compounds and nitrogen-containing compounds; the dispersion medium is one or more of deionized water, ethanol, and isopropanol.
3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the carbon source, heteroatom source and nano-silica template is (20-50):(10-50):(0.5-3), the mass ratio of the carbon source and the dispersion medium is (5-15):(50-100), the hydrothermal reaction temperature is 160-200℃, and the time is 6-12h.
4. The preparation method according to claim 1, characterized in that: In step S2, the spherical precursor is carbonized at high temperature in an inert atmosphere at a temperature of 900-1100℃ for 1-3 hours; the template removal is achieved by etching with acid to remove the silica template; the activation and pore formation are carried out in a N2 / CO2 mixed atmosphere at a temperature of 700-900℃ for 0.5-2 hours to obtain a hierarchical porous carbon microsphere structure with a synergistic distribution of micropores and mesopores; wherein CO2 accounts for 5%-60% of the total volume of the N2 / CO2 mixed gas, and the mixed gas flow rate is 50-500 mL / min.
5. The preparation method according to claim 1, characterized in that: In step S3, the carbon nanotube oxidation pretreatment is carried out by one or more of the following methods: nitric acid treatment, sulfuric acid / nitric acid mixed acid treatment, and hydrogen peroxide treatment. The treatment temperature is 40-80℃ and the treatment time is 1-6h. The dispersion medium is one or more of the following: deionized water, ethanol, and isopropanol.
6. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the hierarchical porous carbon microspheres to the carbon nanotubes after oxidation pretreatment is 100:1-2:1; the mixing and composite conditions are: stirring at room temperature to 60°C for 1-12 hours, supplemented by ultrasonic treatment for 5-60 minutes.
7. The preparation method according to claim 1, characterized in that: In step S4, the second heat treatment is carried out under a nitrogen or argon atmosphere, the heat treatment temperature is 700-900℃, the holding time is 1-2h, and the heating rate is 3-10℃ / min.
8. A carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material prepared by the preparation method according to any one of claims 1-7, characterized in that: The composite electrode material includes hierarchical porous carbon microspheres and carbon nanotubes bridging the surface of the microspheres and between the microspheres. The hierarchical porous carbon microspheres provide ion adsorption sites and mass transfer channels, while the carbon nanotubes construct an electron conduction network.
9. The carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material according to claim 8, characterized in that: The hierarchical porous carbon microspheres have a pore structure with a synergistic distribution of micropores and mesopores, and the pore structure extends through the spherical carbon skeleton.
10. The application of the carbon nanotube-reinforced hierarchical porous carbon microsphere composite electrode material as described in claim 8 or 9 in capacitive deionization, characterized in that: The composite electrode material is used for ion removal in saline systems, wherein the saline system is one or a mixture of brackish water, simulated brine, and industrial saline wastewater. The capacitor deionization operating voltage is 0.8-1.6V, and the ion is Na+. + Cl - Mg 2+ Ca 2+ One or more of them are mixed together.